2016
DOI: 10.1017/age.2016.12
|View full text |Cite
|
Sign up to set email alerts
|

Profitability of Virginia's Agritourism Industry: A Regression Analysis

Abstract: Virginia's growing agritourism industry provides additional income to farms and mitigates risk. This study empirically analyzes the effect of demographic, operational, and financial factors on the profitability of agritourism operations using a primary data set collected from a survey of more than 500 agritourism operations. Results show that greater profitability is associated with operators who are motivated by additional income and have more education, larger operations with a greater percentage of income f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 16 publications
1
20
1
Order By: Relevance
“…Moreover, the majority of researchers focused on previously developed agritourism destinations. Specifically, in the case of the United States, bed and breakfast and commercial farm tours became widespread in the 1980s and 1990s [18], and scholars conducted numerous studies on agritourism in developed tourist destinations [7,26,28]. Similar trends can be observed in Europe, Australia, and some Asian countries [10,[29][30][31][32][33][34].…”
Section: Existing Reviewed Literature On Agritourismmentioning
confidence: 81%
See 1 more Smart Citation
“…Moreover, the majority of researchers focused on previously developed agritourism destinations. Specifically, in the case of the United States, bed and breakfast and commercial farm tours became widespread in the 1980s and 1990s [18], and scholars conducted numerous studies on agritourism in developed tourist destinations [7,26,28]. Similar trends can be observed in Europe, Australia, and some Asian countries [10,[29][30][31][32][33][34].…”
Section: Existing Reviewed Literature On Agritourismmentioning
confidence: 81%
“…However, the pace of agritourism's growth in developing countries, especially in the South Asian countries, is delayed as compared with the pace of that in developed countries [1][2][3][4][5]. Agritourism development is primarily based on farmers' willingness [1,2] and the ability to establish the necessary infrastructure [6][7][8], as well as tourists' interest in visiting such attractions [9][10][11]. More specifically, agritourism development and sustainability depend on supply and demand factors and exploring those factors sheds light on the conditions for agritourism development from the supply and demand perspectives [10,12].…”
Section: Introductionmentioning
confidence: 99%
“…These figures do not include the thousands of other, nonfarm establishments that fall under the definition of agritourism, including farm heritage sites and rural businesses providing agricultural or outdoor-related recreation activities. Farm owners enter the tourism industry motivated primarily by the opportunity to supplement existing income sources (Nickerson, Black, and McCool 2001; McGehee and Kim 2004; Barbieri 2010; George et al 2011; Lucha et al 2016), although nonfinancial reasons are also important motivators (Blank 2002; George et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Research reported by other authors shows that agritourism has a significant and positive impact on the profitability of farms. The impact on profits is highest on small farms, which are the only source of income for their owners [81,82].…”
Section: Conclusion and Discussionmentioning
confidence: 99%